Deveta dežela, podobi pojugoslovanske sedanjosti in antiutopična podoba (evropske?) prihodnosti - Pavičić, Mladen (Slavia Centralis, 2020)
Deveta dežela/The Ninth Country, images of post-Yugoslav present and an anti-utopian image of the (European?) futureThe central theme of this article is the post-Yugoslavic multilinguism of the block settlement Nove Fužine in Ljubljana, as it is presented in the novels Fužinski bluz by Andrej Skubic and Čefurji raus! by Goran Vojnović. The introduction includes some interesting thoughts about Europe, Slovene language and Slavic democratic self-government from the utopian The Ninth Land by Josip Stritar, while the conclusion presents a few thoughts on the modern antiutopian Change Me by Andrej Blatnik, where the dark vision of the future does not concern the Slovene language.
Keywords: Nove Fužine; language of immigrants; Slovene language; sociolekt; utopia; antiutopia